2021
DOI: 10.1111/epi.16875
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged epileptic discharges predict seizure recurrence in JME: Insights from prolonged ambulatory EEG

Abstract: Objective: Markers of seizure recurrence are needed to personalize antiseizure medication (ASM) therapy. In the clinical practice, EEG features are considered to be related to the risk of seizure recurrence for genetic generalized epilepsies (GGE).However, to our knowledge, there are no studies analyzing systematically specific EEG features as indices of ASM efficacy in GGE. In this study, we aimed at identifying EEG indicators of ASM responsiveness in Juvenile Myoclonic Epilepsy (JME), which, among GGE, is ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…A more recent study took a step further to investigate different qualities of EDs associated with seizure relapse following ASM withdrawal. 49 The authors retrospectively analyzed 32 prolonged (22-h) ambulatory EEG recordings from 26 adults with JME to evaluate the predictive value of the total number, frequency, spike density, and mean/ maximum duration of EDs. In the multivariate analysis, the maximum length of ED paroxysm emerged as the only significant marker, with ≥2.68s duration predicting seizure recurrence (specificity = 100%, sensitivity = 93%).…”
Section: Asm Withdrawalmentioning
confidence: 99%
See 2 more Smart Citations
“…A more recent study took a step further to investigate different qualities of EDs associated with seizure relapse following ASM withdrawal. 49 The authors retrospectively analyzed 32 prolonged (22-h) ambulatory EEG recordings from 26 adults with JME to evaluate the predictive value of the total number, frequency, spike density, and mean/ maximum duration of EDs. In the multivariate analysis, the maximum length of ED paroxysm emerged as the only significant marker, with ≥2.68s duration predicting seizure recurrence (specificity = 100%, sensitivity = 93%).…”
Section: Asm Withdrawalmentioning
confidence: 99%
“…In the multivariate analysis, the maximum length of ED paroxysm emerged as the only significant marker, with ≥2.68s duration predicting seizure recurrence (specificity = 100%, sensitivity = 93%). 49…”
Section: Asm Withdrawalmentioning
confidence: 99%
See 1 more Smart Citation
“… 29 In patients with juvenile myoclonic epilepsy, the maximum duration of epileptic discharge sequences is considered an indicator of seizure recurrence. 30 In patients with ischaemic stroke, sharp waves/spikes on follow-up EEG after acute symptomatic seizures positively correlate with seizure recurrence risk. 23 This research identified IEDs as a risk indicator of seizure recurrence in two PSE cohorts (both n = 187).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the study setting in a tertiary adult epilepsy center and the heterogeneity of the 24-h EEG recording delay from epilepsy diagnosis further limited the generalizability of this study’s findings. The prognostic significance of prolonged epileptiform EEG runs in the prediction of seizure remission was recently supported by the results of a study in JME patients, in which ED duration longer than 2.6 s correctly identified patients with seizure relapse within 12 months after paEEG [ 65 ].…”
Section: Eeg Biomarkers Found With Paeeg Recordings Associated With P...mentioning
confidence: 99%